PENGARUH MODEL MIND MAPPING TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL SISWA DI SEKOLAH DASAR - Ersan, Ersan; Marli, Suhardi; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to analyze the influence of the use of Mind Mapping Learning Model on the results of learning social science in the fifth grade students of 41 Sungai Raya Elementary School. The method used is the experimental method. This study used the Pre-Experimental Design design in the form of One Group Pretest-Posttest Design. The research sample in this study were all class V students. Data collection techniques were measurement techniques. The data collection tool used was a test. Based on data analysis, the average post-test results of the experimental class are 79.32, tcount 12.11 and ttable 1.694, because thitung> t table, then Ha is accepted. So, it can be concluded that there was the influence of mind mapping learning models on student learning outcomes. Calculation of the effect size obtained by ES = 1.19 which was classified as high, namely ES> 0.8. It can be said that mind mapping learning has a high influence on social studies learning outcomes in fifth grade students of 41 Sungai Raya Elementary School. Keywords: Learning Outcomes,Mind Mapping, Social Sciences